(untitled) (Proceedings of the European Wave and Tidal Energy Conference, 2023)
Multi-source offshore renewable energy parks, consisting of wind, solar and wave converters, can utilize the available offshore area much more efficiently than single source wind parks. They can also produce power with a higher capacity factor than single source parks, utilizing the available grid connection more efficiently. Dimensioning and financial optimization of such parks will be driven by geographic constraints like available area, water depths, shipping lanes, exclusion zones etc., but also by the available resources of wind, solar and wave power. Another major driver in the optimization will be the electricity price. With the raising share of weather dependent renewables in the electricity mix, the electricity price will become more volatile. Therefore, an optimized design process of a multi-source park should also incorporate a pricing mechanism that can produce hourly electricity prices based on actual weather conditions. The paper will present the results of a numerical model that can integrate solar and wave power in a wind park area as well as optimize the export cable capacity. Battery storage can be added to this multi-source park to shift part of the production to hours with higher electricity prices. A case study has been performed for the planned offshore wind park TNW, North of the Dutch Waddeneilanden. Since such a multi-source park will have an expected lifetime of about 30 years, it will even reach the year 2050, in which weather dependent renewable energy will be much more dominant than today, with far stronger electricity price volatility. For the electricity price calculation, assumptions are made for the installed base of solar, wind and wave power in the whole of The Netherlands, as well as the geographic spread of this installed base over the land area and the offshore exclusive economic zone in the North Sea. This installed base is simplified by concentrating it in about ten locations divided over this area. Other necessary assumptions are the future electricity demand pattern, the future capacity of the interconnections with the surrounding countries and the capacity of the flexible load that will be available at that time (electric cars, electric heaters etc.). From literature, the cost of conventional power fueled by natural gas and/or hydrogen is derived which serves as back up power for hours with low wind, solar and wave power production. Based on all these assumptions, a pricing curve is constructed reaching from sub zero at abundant renewable supply to a maximum value at zero renewable supply. With the model, scenarios of future developments in installed wind, solar and wave power, but also in e.g. electric cars, electric heaters and other flexible loads, can be examined and the sensitivity of the optimization of the multi-source park design can be determined. The relevance of wave power can be determined from the average price per MWh that wave power can earn compared to wind and solar.